PENDUGAAN DAERAH PENANGKAPAN IKAN TENGGIRI (Scomberomorus commerson) BERDASARKAN SUHU PERMUKAAN LAUT DAN KLOROFIL-A DI PULAU TUNDA - Windi Nur Widianingsih; Ferry Dwi Cahyadi; Agung Setyo Sasongko (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
The purpose of this study was to map the potential fishing ground for mackerel (Scomberomorus commerson) from March to June from 2020 to 2022. The method used is by remote sensing with Aqua MODIS imagery to obtain sea surface temperature (SST) and chlorophyll-a. The results showed that there were fluctuating changes in measurements of SST, Chlorophyll-a, and Points which were suspected to be potential locations for mackerel (Scomberomorus commerson) fishing in Tunda Island waters. The value of Sea Surface Temperature (SST) for the last three years, the highest SST of 30.5°C occurredin May 2020 and the lowest (SST) was in June 2020 with a temperature value of around 25.5°C. The value of the concentration of chlorophyll-a in the waters of Tunda Island is very diverse, the highest chlorophyll-a occurs in March and May 2022 with a range of 2.5 mg/L, while the concentration value of chlorophyll-a occurs in May with a value of 0.5 mg/L L. Combining SST and Chlorophyll-a images so as to find the mapping location points for Potential Mackerel (Scomberomorus commerson) Catching Areas, which can be found at coordinates 5° 48'43'S to 106°16'47 E with predictions of the highest abundance of catching points in March namely as many as 19 points of Potential Fishing Areas.